Rancang Bangun Sistem Informasi Geografis pada Aplikasi Mobile Berbasis Standard Web MAP Service Menggunakan J2ME - Nora Nurmatya Grafidth; Harjono Harjono (JUITA : Jurnal Informatika, 2011)
Currently the development of mobile telephone supports GPRS (General Packet Radio service) and java technology is increasingly rapidly. Java application has been widely used on mobile as activity supporting everyday, one of which is used to facilitate communication in the navigation and display information that is geographically. The final assignment is made the application of geographic information system using mobile J2ME in order to make it easy for the user to display a map with the data loaded on-line